Suppression of adaptive NK cell expansion by macrophage-mediated phagocytosis inhibited by 2B4-CD48 - Rui Li; Cristian Camilo Galindo; Dominique Davidson; Huaijian Guo; Ming-Chao Zhong; Jin Qian; Bin Li; Zsolt Ruzsics; Colleen M. Lau; Timothy E. O'Sullivan; Silvia M. Vidal; Joseph C. Sun; et al. (Cell Reports, 2024)
Summary: Infection of mice by mouse cytomegalovirus (MCMV) triggers activation and expansion of Ly49H+ natural killer (NK) cells, which are virus specific and considered to be “adaptive” or “memory” NK cells. Here, we find that signaling lymphocytic activation molecule family receptors (SFRs), a group of hematopoietic cell-restricted receptors, are essential for the expansion of Ly49H+ NK cells after MCMV infection. This activity is largely mediated by CD48, an SFR broadly expressed on NK cells and displaying augmented expression after MCMV infection. It is also dependent on the CD48 counter-receptor, 2B4, expressed on host macrophages. The 2B4-CD48 axis promotes expansion of Ly49H+ NK cells by repressing their phagocytosis by virus-activated macrophages through inhibition of the pro-phagocytic integrin lymphocyte function-associated antigen-1 (LFA-1) on macrophages. These data identify key roles of macrophages and the 2B4-CD48 pathway in controlling the expansion of adaptive NK cells following MCMV infection. Stimulation of the 2B4-CD48 axis may be helpful in enhancing adaptive NK cell responses for therapeutic purposes.